Performance analysis of variable bit rate multiclass services in the downlink of a dynamic complete partitioning round-robin carrier-hopping multirate multi-carrier DS-CDMA system - Wong, T.C. (2014)
IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC